The Airway Microbiome and Metabolome in Preterm Infants: Potential Biomarkers of Bronchopulmonary Dysplasia - Xu, Qi; Yu, Jialin; Liu, Dong; Tan, Qi; He, Yu (Frontiers in Pediatrics, 2022)
Objectives: We investigated the genomic and metabolic characteristics of the airway microbiome in mild, moderate, severe, and non-bronchopulmonary dysplasia (BPD) preterm infants and explored possible mechanisms underlying BPD. Methods: Twenty-eight preterm infants with gestational age ≤34 weeks and intubated within 24 hours after birth were enrolled. According to the severity of BPD, the patients were divided into mild, moderate and severe BPD groups, and the non-BPD group was the control group. Tracheal aspirates were obtained at intubation and on day7 after birth. The bacterium in the aspirates were sequenced by 16S rRNA, and the metabolomics of the aspirates were identified by high performance liquid chromatography-quadrupole time of flight mass spectrometry (UHPLC-Q-TOF/MS). The correlation between the differential metabolite and differential bacteria was investigated using Pearson’s correlation coefficient corrected for gestational age and birth wight and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Results: There were significant differences in the diversity and composition of airway microbiome and metabolome between severe, moderate and mild BPD and non-BPD premature infants. At birth (day 1), the difference was more pronounced than at day 7. The diversity of airway microbial community decreased, the abundance of Stenostomonas increased, and the increased level of SN-glycerol 3-phosphate ethanolamine was positively correlated with the severity of BPD. There was a significant positive correlation between the abundance of Stenotrophomonas and the level of Sn-glycerol 3-phosphate ethanolamine. Conclusion: Decreased diversity of the airway microbiome, increased abundance of Stenotrophomonas, and increased level of sn-glycerol 3-phosphoethanolamine may have potential as biomarkers for BPD. The occurrence and severity of BPD are closely related to Stenotrophomonas, which may influence the composition of the lower airway microbiome through its metabolite sn-glycerol 3-phosphate ethanolamine, and may be the triggering factor of the disease. The causal relationship needs further study.